Systematic Review: Kemampuan Representasi Matematika dalam Pendidikan Selama 2019-2024 - Maulana, Bagus Surya; Junaedi, Iwan; Munahefi, Detalia Noriza; Masrukan; Cahyono, Adi Nur (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2025)
Mathematical representation encompasses verbal, visual, and symbolic forms, allowing students to articulate and manipulate mathematical ideas effectively. The review indicates that students with strong representation abilities perform better academically, as these skills facilitate deeper comprehension and application of mathematical principles. A systematic review of mathematics representation ability in education during 2019-2024 in this study from 2019 to 2024, Data collection was carried out by reviewing or reviewing all articles on mathematics representation ability in education published in the period 2019-2024. The articles used in this study were 3 articles from Scopus, and 2 articles from Google Scholar from international and national journals with the help of Publish or Perish software and VOSViewer. The results of this literature review suggest that specific research needs to be conducted on how to improve mathematics representation abbility, the school levels tested, as well as their applicability in education.